Teenage suicide - Goldman, M. Nikki 1950- (New York Benchmark Books, 1996)
Discusses the problem of teenage suicide, including information on warning signs, myths about suicide, prevention, and the right to die debate.
Keywords: Teenagers -- Suicidal behavior -- Juvenile literature; Suicide -- Prevention -- Juvenile literature